2012
DOI: 10.1073/pnas.1216080109
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function Na v 1.8 mutations in painful neuropathy

Abstract: Painful peripheral neuropathy often occurs without apparent underlying cause. Gain-of-function variants of sodium channel Na v 1.7 have recently been found in ∼30% of cases of idiopathic painful small-fiber neuropathy. Here, we describe mutations in Na v 1.8, another sodium channel that is specifically expressed in dorsal root ganglion (DRG) neurons and peripheral nerve axons, in patients with painful neuropathy. Seven Na v 1.8 mutations were identified in 9 subjects within a series of 104 patients with painfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
301
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 384 publications
(321 citation statements)
references
References 39 publications
7
301
1
4
Order By: Relevance
“…Despite their well-established roles in nociception, the mechanisms by which Na v 1.7 and Na v 1.8 isoforms specifically contribute to neuropathic pain are still under debate. On the one hand, knocking down Na v 1.8 prevents neuropathic pain in mice (40), Na v 1.7 accumulates in human painful dental pulp (15), and gain-of-function mutations of Na v 1.7 and Na v 1.8 are linked to exaggerated pain in humans (12,13). A recent simulation study suggested that Na v 1.7 and Na v 1.8 may act synergistically to increase the amplitude of subthreshold oscillations and increase the frequency of repetitive firing in the periphery (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their well-established roles in nociception, the mechanisms by which Na v 1.7 and Na v 1.8 isoforms specifically contribute to neuropathic pain are still under debate. On the one hand, knocking down Na v 1.8 prevents neuropathic pain in mice (40), Na v 1.7 accumulates in human painful dental pulp (15), and gain-of-function mutations of Na v 1.7 and Na v 1.8 are linked to exaggerated pain in humans (12,13). A recent simulation study suggested that Na v 1.7 and Na v 1.8 may act synergistically to increase the amplitude of subthreshold oscillations and increase the frequency of repetitive firing in the periphery (41).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring mutations in SCN9A, the gene encoding Na v 1.7, lead to either congenital insensitivity or severe episodic hypersensitivity to pain (9)(10)(11). In addition, Na v 1.7 and Na v 1.8 gain-offunction mutations in painful peripheral neuropathy syndromes were recently described (12,13). Not only are Na v 1.7 and Na v 1.8 important in inherited pain disorders, but also in acquired pain disorders, where their increased expression has already been linked to diverse chronic pain symptoms (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…SFN is also associated with a widening spectrum of systemic diseases; the most recent disease to be associated, in 2016, is Elhers-Danlos syndrome 105 . In many patients, SFN is idiopathic, but pathogenic mutations in genes that encode for various sodium channels have been identified in some patients [106][107][108] . A correlation between specific mutations and painful and autonomic symptoms has been reported 109 , and novel mutations in COL6A5 have been found in patients with neurogenic itch and SFN 110 .…”
Section: Ehlers-danlos Syndromementioning
confidence: 99%
“…Two gain-of-function mutations in SCN10A, which encode Na V 1.8 (found in patients with painful neuropathy) enhance the channel's response to depolarisation and produce hyperexcitability in DRG neurons. 8 Na V 1.9 is also a desirable drug target (as shown using mouse models) and is also expressed in DRG neurons but has proved difficult to functionally express in heterologous systems and is therefore challenging to study. 9 TRPV1 (a member of the TRP superfamily of excitatory ion channels that bind vanilloids) is predominantly expressed by nociceptors and is therefore also a popular pain relief target, 10 but in clinical trials, drugs inhibiting the TRPV1 channel cause hyperthermia and decreased sensitivity to painful levels of heat.…”
Section: Pain Target Classesmentioning
confidence: 99%